Minat dan Motivasi Mahasiswa Pendidikan Bahasa Jepang Angkatan 2022 UNNES Untuk Bekerja Di Jepang: The Interest and Motivation of 2022 Japanese Education Students at UNNES to Work in Japan - Shafly, Abiyyu; Sanjaya, Muhamad Bangkit; Candra, Ramanda Tirtya; Shanty Dewi, Rafael Grace Wisda; Kurniawan, Andri (Undiksha Press, 2025)
Working abroad is a choice for some individuals, influenced by various factors. Interest and motivation vary from person to person, especially among students who face numerous factors affecting their decision to work abroad, such as economic, socio-cultural, technological, and educational aspects. This study aims to identify and analyze the interest and motivation of 2022 Japanese Language Education students at Universitas Negeri Semarang (UNNES) in working in Japan. Using a descriptive quantitative approach with a survey method, 40 students participated as respondents. Data were collected through a questionnaire designed to measure the level of interest and various influencing factors, including economic, cultural, and educational aspects. The results indicate that 9 out of 15 questions revealed that the students agreed on their interest and motivation to work in Japan, influenced by factors such as motivation, interest, socio-cultural aspects, technology, and education.